Meningkatkan Kemampuan Menulis Karangan Deskripsi melalui Penerapan Teknik Menulis Objek Langsung pada Siswa Kelas IV SDN 1 Peteluan Indah - Suryanirmala, Neni (Lembaga Yasin AlSys, 2022)
The purpose of this study was to improve the ability to write descriptive essays through the application of direct object writing techniques to fourth grade students of SDN 1 Peteluan Indah in the 2021/2022 school year. Through classroom action research which was carried out in 2 cycles, which consisted of 3 meetings in the first cycle and 2 meetings in the second cycle. This research uses descriptive quantitative data analysis method. The indicator of success is the result of writing student descriptions in terms of increasing gain through the normalized <g> gain test, at least in the medium category. Based on the results of data analysis, it can be concluded that the application of direct object writing techniques can improve the ability to write descriptive essays for fourth grade students of SDN 1 Peteluan Indah in the 2021/2022 school year. The improvement of students' writing descriptive essay ability can be seen from an increase of 14.07 (the average value before the study was 52.74 to 68.57 after the study). A significant increase can be seen from the results of the normalized gain test <g> before the study and after the study, which is 0.407 which is categorized as